Rasmus Rask og det italienske verbalsystem - Jensen, Viggo Bank (Ny forskning i grammatik, 2017)
The great Danish linguist Rasmus Rask (1787-1832) published a short Italian grammar in 1827. His work is analytic and discursive. In my article I shall present and discuss Rask’s exposition of the Italian verbal system. I shall focus on two elements: 1) Rask’s use of a Danish terminology which has some similarities with Reichenbach’s system; 2) Rask’s allocation of condizionale as an indicative tense, in contrast to a long Italian grammatical tradition of having condizionale as an independent mood. I shall show that Rask’s consistent use of his tense terminology throws a critical light on the Reichenbach system and further argue that the study of Rask’s treatment of condizionale can give us a basis for some clarification and inspiration in the didactics of teaching the Italian language.